Study of the production of and hadrons in pp collisions and first measurement of the branching fraction *Supported by CERN and national agencies: CAPES, CNPq, FAPERJ and FINEP (Brazil); NSFC (China); CNRS/IN2P3 (France); BMBF, DFG, HGF and MPG (Germany); INFN (Italy); FOM and NWO (The Netherlands); MNiSW and NCN (Poland); MEN/IFA (Romania); MinES and FANO (Russia); MinECo (Spain); SNSF and SER (Switzerland); NASU (Ukraine); STFC (United Kingdom); NSF (USA). The Tier1 computing centres are supported by IN2P3 (France), KIT and BMBF (Germany), INFN (Italy), NWO and SURF (The Netherlands), PIC (Spain), GridPP (United Kingdom). Individual groups or members have received support from EPLANET, Marie Skłodowska-Curie Actions and ERC (European Union), Conseil général de Haute-Savoie, Labex ENIGMASS and OCEVU, Région Auvergne (France), RFBR (Russia), XuntaGal and GENCAT (Spain), Royal Society and Royal Commission for the Exhibition of 1851 (United Kingdom). (January 2016) - Aaij, R.; Adeva, B.; Adinolfi, M.; Affolder, A.; Ajaltouni, Z.; Akar, S.; Albrecht, J.; Alessio, F.; Alexander, M.; Ali, S.; Alkhazov, G.; Alvarez Cartelle, P.; et al.
Abstract: The product of the differential production cross-section and the branching fraction of the decay is measured as a function of the beauty hadron transverse momentum, p T, and rapidity, y . The kinematic region of the measurements is p T < 20 GeV/ c and 2.0 < y < 4.5. The measurements use a data sample corresponding to an integrated luminosity of 3fb −1 collected by the LHCb detector in pp collisions at centre-of-mass energies in 2011 and in 2012. Based on previous LHCb results of the fragmentation fraction ratio the branching fraction of the decay is measured to be where the first uncertainty is statistical, the second is systematic, the third is due to the uncertainty on the branching fraction of the decay B̅ 0 → J/ ψ K̅*(892) 0, and the fourth is due to the knowledge of . The sum of the asymmetries in the production and decay between and is also measured as a function of p T and y . The previously published branching fraction of, relative to that of, is updated. The branching fractions of are determined.